Financial Openness, Domestic Financial Development and Credit Ratings - Andreasen, E (Elsevier Ltd, 2016)
This article shows that financial openness significantly affects corporate and sovereign credit ratings and that the magnitude of this effect depends on the level of development of the domestic financial market. Issuers located in less financially developed economiesi stand to benefit the most from opening up their capital accounts, whereas the impact of this effect decreases as the level of development of the domestic capital market improves. © 2015 Elsevier Inc.